CONSUMER EXPERIENCES, TIME SAVING ORIENTATION, AND PRICE SAVING ORIENTATION ON ACTUAL BEHAVIOR TO USE APPLICATION ONLINE DELIVERY FOOD GRABFOOD THROUGH CONVENIENCE MOTIVATION - Giningroem, Dewi Sri Woelandari Pantjolo; Setyawati, Novita Wahyu; Wijayanti, Murthi; Hadita, Hadita (Universitas Pelita Harapan, 2022)
The purpose of this study was to determine the effect of consumer experiences, time saving orientation, and price saving orientation on actual behavior using grab food through convenience motivation as an intervening variable. This study uses a quantitative approach and a pilot study of 30 respondents was conducted to test the research instrument. The object of this research is the people of Bekasi City by using a sample of 136 respondents. The data analysis technique in this study uses regression uing the SPSS version 24 application. The results show that consumer experiences, time saving orientation, and price saving orientation variables have a significant effect on actual behavior and convenience motivation in using grab food. Meanwhile, convenience motivation is able to mediate consumer experiences, time saving orientation, and price saving orientation towards actual behavior in using grab food.